Peran Self Regulatory Organization (Sro) Meningkatkan Perlindungan Hak Investor Pada Saat Covid-19 - Wel Effendi, Afrizaldi; Kartika Sari, Indah; Mukhairani, Mukhairani (Jurnal Akuntansi UMMI, 2023)
The purpose of this study is to find out SRO's efforts to protect investors' interests during COVID-19. This study uses a descriptive qualitative methodology. Several books or literature from previous studies became the source of data for this investigation. The findings show that the SRO continues to pay close attention to developments in market capitalization and has also issued a number of policies, one of which allows issuers or companies listed on the Indonesian Stock Exchange to be able to buy back shares without having to go through a General Meeting of Shareholders (GMS), with the intention of providing legal protection and legal certainty for investors.